The effect of chard (Beta vulgaris L. var. cicla) on the skin of streptozotocin induced diabetic rats - (:unkn) unknown (My University, 1998)
Chard (Beta vulgaris L. var. cicla) is one of the plants used as hypoglycaemic agent by diabetics in Turkey and it has been reported to reduce blood glucose. The purpose of this study was to investigate the effect of feeding chard on diabetes induced impairments in rat skins. Uncontrolled induced diabetes caused significant increases in nonenzymatic glycosylation of skin proteins, lipid peroxidation and blood glucose. Administration of chard extract inhibited these effects except the increase in lipid peroxidation. SDS-polyacrylamide gel electrophoresis revealed no significant differences in any protein bands between any of the groups. The data indicate that the use of chard may be effective in preventing or at least retarding the development of some diabetic complications.
Keywords: Female; Animals; Male; Skin; Glycosylation; Rats; Lipid Peroxidation; Plant Extracts; Plants, Medicinal; Hypoglycemic Agents; Electrophoresis, Polyacrylamide Gel; Blood Glucose; Diabetes Mellitus, Experimental; Diet; Body Weight